Exploring Students' Engagement in An Internship Accounting Degree Program at A Public University in Sarawak: The Application of I-E-O Model - Joseph, Corina; Salleh, Siti Maliza; Norizan, Saifulrizan; Yasin, Siti Aimi Mohamad; Ismail, Nur Izyan (Business and Economic Research, 2024)
The objective of this paper is to explore the factors that promote the effectiveness of students’ engagement in an internship accounting program at University X in Sarawak using the Astin's input-environment-output (I-E-O) model. An online open-ended questions survey was distributed to the 74 accounting internship students in February 2024 to gather their reflection on the engagement in the internship program. The inputs element of students’ engagement includes academic performance, course curriculum, and internship briefing. The themes identified in this paper related to environment include workplace environment, work assignment and exposure, student learning advancement, self-reward, feedback mechanism, and mentorship program. The findings revealed the outputs/outcomes derived from students’ engagement include self-development and enhancement, knowledge enhancement, adaptability to working environment, networking and career opportunities, and exposures. The new insights from this paper includes internship briefing, self-reward, feedback mechanism and cultural diversity exposures. The findings offer significant implications for employers, students and supervisors. This research suggests a revised I-E-O framework that depicts student engagement as a complex construct with a significant impact on various aspects of a student's academic and personal life. Finally, a new I-E-O Framework is presented in this paper.